Precision in treatment evaluation: importance of minimal clinically important differences (MCIDs) of outcome measures for autoimmune blistering diseases - Tseng, Henry; Stone, Corey; Murrell, Dédée F. (Frontiers in Immunology, 2023)
Autoimmune blistering diseases (AIBDs) comprise a group of rare conditions marked by autoantibodies that specifically target intercellular adhesion molecules. Despite the progress made in comprehending the disease and the increasing number of treatment options available, there is still no definitive cure for AIBDs such as pemphigus, and it continues to have a devastating impact on those affected. The challenges in achieving new approved therapies for AIBDs are complex and multifaceted. One significant obstacle was the prior lack of validated and standardized outcome measures, which are crucial for ensuring precise comparisons between new and traditional therapies. This gap in knowledge has prompted the development of minimal clinically important differences (MCIDs), which enable efficient and reliable comparison of therapeutic outcomes between trials. MCID is defined as the minimum difference in an outcome measure that indicates a clinically significant improvement/deterioration in disease severity. Additionally, MCIDs provide a patientcentered approach to evaluating treatment efficacy, by considering whether patients experience a subjective improvement in their symptoms. Therefore, this literature review will examine the derivation and significance of MCIDs for various scoring systems in AIBDs.